APPLICATION OF C 4.5 ALGORITHM METHOD FOR DETERMINING THE “BIDIK MISI” SCHOLARSHIP ADMISSION IN INSTITUTE OF INFORMATICS AND BUSINESS (IIB) DARMAJAYA - Halimah Halimah; Deppi Linda; TM Zaini; Agus Rahardi (Proceeding International Conference on Information Technology and Business, 2020)
“Bidik Misi’ Scholarship is one of the educational scholarships provided by the Government of the Republic of Indonesia for prospective students who had a high academic potency with underprivileged condition. The problem statement of this research was that IIB Darmajaya still used a manual method to determine the students who were eligible to achieve the scholarship so that it did not meet the target and took a long time. The objective of this study was designing C 4.5 algorithm for determining the prospective students who were eligible to achieve the “Bidik Misi” Scholarship from IIB Darmajaya. The method used in this study was Rational Unified Process (RUP). The tools used in this study were Use Case Diagrams, Activity Diagrams, Sequence Diagrams, and Class Diagrams. Theb programming languages used in this study were and the PHP and MySQL. The result of this study showed that this system was not only able to determine the feasibility of the prospective students who were eligible to achieve “Bidik Misi” Scholarship but it was also able to facilitate the committee to work faster and more efficient.Keywords: “Bidik Misi” Scholarship, Rational Unified Process (RUP), C 4.5 Algorithm